1990
DOI: 10.1016/0736-5748(90)90032-w
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in uptake and release on l‐[3H]noradrenaline in brain slices of senescence accelerated mouse

Abstract: High K+ and N-methyl-D-aspartate (NMDA) evoked L-[3H]noradrenaline (NA) release to a similar degree in the brain slices of 1-month-old senescence-accelerated resistant mice (SAM-R/1) and senescence-accelerated prone mice (SAM-P/8). However, 30 mM KCl-induced L-[3H]NA release significantly diminished in SAM-P/8 from 3 to 12 months without changing in SAM-R/1. In addition, NMDA-induced L-[3H]NA release was also reduced at 3 months and lowered to a level of spontaneous release at 12 months in SAM-P/8, but no age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Biochemical studies done by Nomura and his colleagues demonstrated that there was an age-associated reduction in K ? -or NMDA-evoked release of noradrena1in and an increase in a 2 receptors in the brain of SAMP8 [22,23]. From these results, Miyamoto suggested that the deterioration in the noradrenergic system may participate in reduced anxiety-like behavior [15].…”
Section: Samp8mentioning
confidence: 90%
See 1 more Smart Citation
“…Biochemical studies done by Nomura and his colleagues demonstrated that there was an age-associated reduction in K ? -or NMDA-evoked release of noradrena1in and an increase in a 2 receptors in the brain of SAMP8 [22,23]. From these results, Miyamoto suggested that the deterioration in the noradrenergic system may participate in reduced anxiety-like behavior [15].…”
Section: Samp8mentioning
confidence: 90%
“…Cerebral cortical [ 3 H]MK-801 binding for N-methyl-D-aspartate (NMDA) receptor/channels in the SAMP8 mouse was lower than that in the SAMR1 mouse, indicating that NMDA receptor functions seem to be deficient in neurons of the SAMP8 mouse brain [51]. NMDA-induced release of [ 3 H]acetylcholine (ACh) and [ 3 H]noradrenaline (NA) was markedly reduced in the brains of SAMP8 mice [23,52]. Since NMDA receptor/ channels are found on both soma and terminals of ACh and NA-containing neurons, these results in the brains of SAMP8 mice strongly suggest functional deterioration of glutamatergic, cholinergic, and noradrenergic neurotransmission in the SAMP8 brain [53].…”
Section: Neurochemical and Neuropharmacological Studiesmentioning
confidence: 97%
“…This morphological analysis was followed by a series of studies focusing on alterations of the cell membrane or on the numbers of neurotransmitter receptors (binding sites) (Flood et al, 1992(Flood et al, , 1993Kitamura et al, 1989Kitamura et al, , 1992Nomura et al, 1996Nomura et al, , 1997Zhao and Nomura, 1990;Zhao et al, 1992). Age-related changes were found in receptors for N-methyl-D-aspartate (NMDA), acetylcholine (M 1 ), serotonin, dopamine, opioids, and ␥-aminobutyric acid (GABA), as well as in ␣-adrenoreceptors.…”
Section: Dendrites/synapses/receptors/membranesmentioning
confidence: 98%
“…SAMP8 presented not only similar characteristics to aged humans, such as shorter lifespan, lordosis, reduced physical activity, and hair loss [46,47], but also some neurodegenerative features, such as early onset of learning and memory deficits [48], altered emotions and abnormal circadian rhythm [49,50], neuronal cell loss [51], and reduction in the release of neurotransmitters in the brain [52,53]. Besides, impairment of mitochondrial functions has been shown in SAMP8 brain at a relatively early age compared to SAMR1 mice [29].…”
Section: Samp8 Postulated As An Early Model Of Alzheimer's Diseasementioning
confidence: 99%